2011
DOI: 10.1016/j.vetpar.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel Cryptosporidium genotypes in kangaroos from Western Australia

Abstract: 13A total of 763 faecal samples were collected from western grey kangaroos (Macropus 14 fuliginosus) in Western Australia and screened for the presence of Cryptosporidium by PCR at 15 the 18S ribosomal RNA (rRNA) locus. Samples that were positive at the 18S locus were also 16 amplified at the actin locus. The overall prevalence was 9.3% (71/ that requires further analyses to confirm its species status. 25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Our estimate of prevalence of Giardia in wild Tasmanian devils (24.1%) is higher than prevalence estimates for mainland Australian marsupials (range 1.3–13.8%) [8, 13, 15, 16], but sits within the range of prevalence estimates for Tasmanian marsupials (6.25–61.5%) [46]. Our 24.1% prevalence estimate for wild devils was also higher than previous prevalence estimates of Giardia in devils of 8.3% ( n = 12) [24] and 6.0% ( n = 32) [23].…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Our estimate of prevalence of Giardia in wild Tasmanian devils (24.1%) is higher than prevalence estimates for mainland Australian marsupials (range 1.3–13.8%) [8, 13, 15, 16], but sits within the range of prevalence estimates for Tasmanian marsupials (6.25–61.5%) [46]. Our 24.1% prevalence estimate for wild devils was also higher than previous prevalence estimates of Giardia in devils of 8.3% ( n = 12) [24] and 6.0% ( n = 32) [23].…”
Section: Discussionmentioning
confidence: 58%
“…This study found a 45.1% prevalence of Cryptosporidium in wild Tasmanian devils. This value is higher than prevalence estimates of Cryptosporidium in other Australian marsupials, which range from 6.7% to 12.2% [6, 811]. Screening at secondary loci resulted in low detection, with only two samples successfully amplified at the actin locus, and no samples amplified at the gp60 locus.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…scrofarum , and C . andersoni [11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23]. To date, in humans in Australia, C .…”
Section: Introductionmentioning
confidence: 99%